2016
DOI: 10.1002/adma.201505119
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactive and Metal‐Platable Copolymer Inks for High‐Throughput, Room‐Temperature Printing of Flexible Metal Electrodes for Thin‐Film Electronics

Abstract: Photoreactive and metal-platable copolymer inks are reported for the first time to allow high-throughput printing of high-performance flexible electrodes at room temperature. This new copolymer ink accommodates various types of printing technologies, such as soft lithography molding, screen printing, and inkjet printing. Electronic devices including resistors, sensors, solar cells, and thin-film transistors fabricated with these printed electrodes show excellent electrical performance and mechanical flexibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 41 publications
2
70
1
Order By: Relevance
“…The data regarding 4 d cell proliferation indicated that the cell spreading depends on the presence of a hydrophobic poly(NIPAM) domain. In order to solidify the deposited poly(NIPAM‐ co ‐ESEMA) film in endothelial growth medium containing water as a main cultivation ingredient, BPMA (5 mol%) was copolymerized as a cross‐linking component in which the benzoyl group is known to decompose to give a free radical . HUVECs plated on poly(NIPAM‐ co ‐ESEMA) films were observed by a day using phase contrast microscopy and we confirmed the proliferation (spreading) of the cells as dark part (adhered) (Figure ).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The data regarding 4 d cell proliferation indicated that the cell spreading depends on the presence of a hydrophobic poly(NIPAM) domain. In order to solidify the deposited poly(NIPAM‐ co ‐ESEMA) film in endothelial growth medium containing water as a main cultivation ingredient, BPMA (5 mol%) was copolymerized as a cross‐linking component in which the benzoyl group is known to decompose to give a free radical . HUVECs plated on poly(NIPAM‐ co ‐ESEMA) films were observed by a day using phase contrast microscopy and we confirmed the proliferation (spreading) of the cells as dark part (adhered) (Figure ).…”
Section: Resultssupporting
confidence: 52%
“…In order to solidify the poly(NIPAM‐ co ‐ESEMA) film in endothelial growth medium containing water as the main cultivation ingredient, 4‐benzoylphenyl methacrylate (BPMA) was copolymerized as a cross‐linking component via a photo‐induced radical reaction following a similar procedure. 4 mg of poly(NIPAM‐ co ‐ESEMA‐ co ‐BPMA) was dissolved in methanol (1 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Since the capping agent promotes an anisotropic directional growth to form the shape of a nanowire, its role is important for the synthesis of CuNW. Therefore, various capping agents were studied including ethylenediamine, hexadecylamine, octadecylamine, and other polymeric materials . Especially, Mohl et al demonstrates a synthesis of ultralong CuNW by using a new hydrothermal method in the presence of hexadecylamine (HDA) .…”
mentioning
confidence: 99%
“…More recently, several advances in polymer‐assisted ELD16, 17, 18 have been accomplished for the fabrication of highly conductive metal structures for flexible and stretchable interconnects,19, 20, 21, 22 supercapacitors,23, 24 conductive textiles,25, 26 and optoelectronic devices 27, 28. The polymer‐assisted ELD typically involves three major steps: surface modification of functional polymer anchoring layers, loading of catalyst moieties to the polymer anchoring layer by ion exchange, and site‐selective metal electroless deposition.…”
mentioning
confidence: 99%